TMBIM6/BI-1 contributes to cancer progression through assembly with mTORC2 and AKT activation - Hyun-Kyoung Kim (Nature Portfolio, 2020)
TMBIM6, a member of the transmembrane BI-1 motif-containing family of proteins, is overexpressed in many cancer types. Here, the authors show that TMBIM6 regulates AKT activation through mTORC2 assembly and ribosome association and identify an antagonist of TMBIM6 with anti-tumor properties.